2011
DOI: 10.1371/journal.pone.0016728
|View full text |Cite
|
Sign up to set email alerts
|

RAPD and Internal Transcribed Spacer Sequence Analyses Reveal Zea nicaraguensis as a Section Luxuriantes Species Close to Zea luxurians

Abstract: Genetic relationship of a newly discovered teosinte from Nicaragua, Zea nicaraguensis with waterlogging tolerance, was determined based on randomly amplified polymorphic DNA (RAPD) markers and the internal transcribed spacer (ITS) sequences of nuclear ribosomal DNA using 14 accessions from Zea species. RAPD analysis showed that a total of 5,303 fragments were produced by 136 random decamer primers, of which 84.86% bands were polymorphic. RAPD-based UPGMA analysis demonstrated that the genus Zea can be divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 39 publications
3
24
1
Order By: Relevance
“…In general, however, many investigators have found that phylogenies based on such arbitrarily amplified markers are highly concordant with, but better resolved than those based on plastid or ITS sequences and/or restriction sites ([29], [31][36] for AFLPs, [28], [37] for RAPDs, [38][40] for ISSRs). Rieseberg [27] found that 91% of 220 RAPD markers used to study interspecific relationships in Helianthus appeared to reflect homologous markers; Ipek et al [30] found that 95% of AFLP amplicons in garlic were identical or highly homologous to the typical marker for that band.…”
Section: Methodsmentioning
confidence: 99%
“…In general, however, many investigators have found that phylogenies based on such arbitrarily amplified markers are highly concordant with, but better resolved than those based on plastid or ITS sequences and/or restriction sites ([29], [31][36] for AFLPs, [28], [37] for RAPDs, [38][40] for ISSRs). Rieseberg [27] found that 91% of 220 RAPD markers used to study interspecific relationships in Helianthus appeared to reflect homologous markers; Ipek et al [30] found that 95% of AFLP amplicons in garlic were identical or highly homologous to the typical marker for that band.…”
Section: Methodsmentioning
confidence: 99%
“…In some allopolyploids, the different genomes from parents may occur divergent changes and different degrees of diplodization (Liu and Wendel 2002), probably due to the discrepant stability of parental genome. In this study, Z. perennis genome is more stable than that of maize in four allopolyploids, and possible explanations for our observations include: (a) the phylogenetic analysis shows that Z. perennis is more primitive than maize (Wang et al 2011), therefore, the inherent stability probably exist in Z. perennis genome as a result from long-term evolution; (b) recent studies demonstrate maize genome has tetraploid origin (Gonzalez and Poggio 2011), ''A'' and ''B'' genome probably exist partial homology (Molina et al 2012); (c) for the two allotriploids, the haploid genome of maize can hardly perform the homologous chromosome paring; (d) different genomes in one nucleus may lead to the disordered expression of Phs1 and Pam1, which play important roles on chromosome paring (Molina et al 2012).…”
Section: Different Genome Effects On Meiotic Pairingmentioning
confidence: 60%
“…The results suggest Z. perennis cytoplasm may give a relatively relaxed environment especially for maize genome. The possible reasons include: (a) the presence of foreign nuclear genome in cytoplasm from the male parent can result in nuclear-cytoplasm incompatibility (Wang et al 2010;Cui et al 2012) and maternal enzymatic system may treat the male chromosomes as exogenous intruders (Hu et al 2013), thus, gene structure variation, aneuploidy and chromosomes structure variation as well as meiosis confusion can potentially occur, comparing to Z. perennis cytoplasm, maize cytoplasm probably has a stronger defense system; (b) Z. perennis is more primitive than maize (Wang et al 2011), and the cytoplasm may have a greater containment than maize; (c) Z. perennis cytoplasm probably has a less negative influence on Phs1 and Pam1 than maize cytoplasm. Additional, interactions can occur between nuclear and cytoplasm followed by loss of genes from both nuclear genome and plasmon (Rand et al 2004), which suggests genome stability also may be affected by interactions between different genome composition and cytoplasm (Cui et al 2012), different results in allotriploids and allotetraploids conform to this speculation.…”
Section: Nuclear-cytoplasmic Interactions Effects On Meiotic Pairingmentioning
confidence: 99%
“…An improved de novo assembly and annotation of a maize reference genome have been recently conducted [14]. To investigate the wide diversity of maize genotypes, few studies on ITS sequencing [15,16] and microsatellites or simple sequence repeats [17,18] have been published. The phylogenetic relationships of Zea species inferred from ITS sequences were demonstrated to be highly concordant with Random Amplified Polymorphic DNA (RAPD) evidence [16,19].…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the wide diversity of maize genotypes, few studies on ITS sequencing [15,16] and microsatellites or simple sequence repeats [17,18] have been published. The phylogenetic relationships of Zea species inferred from ITS sequences were demonstrated to be highly concordant with Random Amplified Polymorphic DNA (RAPD) evidence [16,19]. The main objective of this study was to identify a molecular marker or a haplotype-specific signature sequence that can be used to distinguish the genomes of two Egyptian maize hybrids, M10 and M321M321.…”
Section: Introductionmentioning
confidence: 99%